Protective effect of lycopene on gentamicin-induced oxidative stress and nephrotoxicity in rats - Karahan, I; Atessahin, A; Yilmaz, S; Çeribasi, AO; Sakin, F (Elsevier Ireland Ltd, 2005)
A potential therapeutic approach to protect or reverse gentamicin-induced oxidative stress and nephrotoxicity would have more importance for clinical consequences. Therefore, the present study was designed to investigate the possible protective effects of lycopene against gentamicin-induced renal damage in rats. Male Sprague-Dawley rats were divided into four groups of six rats in each one; first group served as control. The other groups were treated intraperitoncally with gentan-ticin alone (100 mg kg(-1) per day) for six successive days, gentamicin for 6 days following 10 days of orally lycopene (4 mg kg(-1) per day) pre-treatment and 6-days of simultaneous lycopene and gentamicin. Biochemical and histopathological examinations were utilized for evaluation of the oxidative stress and renal nephrotoxicity. Creatinine, urea, Na+ and K+ levels in plasma and malondialdehyde (MDA), reduced glutathione (GSH) levels and glutathione peroxidase (GSH-Px) and catalase (CAT) activities were determined in kidney tissue. Administration of gentamicin to rats induced a marked renal failure, characterized by a significant increase in plasma creatinine and urea concentrations. The animals treated with gentamicin alone showed a significantly higher kidney MDA and lower GSH-Px and CAT activities but unaffected GSH concentrations when compared with the control group. Pre-treatment with lycopene produced amelioration in biochemical indices of nephrotoxicity in plasma. However, little changes were observed in the kidney MDA and GSH levels and GSH-Px and CAT activities when compared with the gentamicin treated group. The histological structures of the renal proximal tubules showed similar patterns. On the other hand, administration of simultaneous lycopene to rats produced amelioration in MDA and GSH levels and GSH-Px and CAT activities when compared with gentamicin group. In addition, simultaneous lycopene was found to reduce the degree of kidney tissue damage in histopathological findings. These results indicate that specially simultaneous treatment of lycopene might have produced amelioration in biochemical indices and oxidative stress parameters against gentamicin-induced nephrotoxicity, but pre-treatments with lycopene had no beneficial effects on these parameters. It was concluded that lycopene as a novel natural antioxidant might have protective effects against gentamicin-induced nephrotoxicity and oxidative stress in rats. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: gentamicin; lycopene; oxidative stress; nephrotoxicity; histopathology